Conocimientos y cumplimiento del lavado de manos en personal de enfermería del servicio de emergencia. Hospital Belén Lambayeque - Dávila Burgos, Samira Sujei Elizabeth (2019)
The present cross-sectional descriptive type research was conducted in the emergency service of the Belén de Lambayeque Hospital between the months of January to July 2018 with the purpose of determining the relationship between the level of knowledge and the degree of compliance with the washing of hands in the nursing staff, of the emergency area of the Belén Lambayeque Hospital, the sample universe was constituted by 17 nurses who met the established inclusion criteria, to collect the data a questionnaire was used to determine the level of knowledge and a Guide Non-participant Observation Check List type to determine compliance. The chi-square statistical test was used for the statistical analysis, concluding that the highest percentage of nurses in the Emergency Service (70.6%), presents a medium level of knowledge; 94,1% of the nurses in the emergency service presented inadequate compliance with regard to handwashing; There is not a relation between the level of knowledge and the degree of compliance (p = 0.118).